CHLOROPLAST UNUSUAL POSITIONING1 Is Essential for Proper Chloroplast Positioning - Oikawa, Kazusato; Kasahara, Masahiro; Kiyosue, Tomohiro; Kagawa, Takatoshi; Suetsugu, Noriyuki; Takahashi, Fumio; Kanegae, Takeshi; Niwa, Yasuo; Kadota, Akeo; Wada, Masamitsu (The Plant cell, 2003)
The intracellular distribution of organelles is a crucial aspect of effective cell function. Chloroplasts change their intracellular positions to optimize photosynthetic activity in response to ambient light conditions. Through screening of mutants of Arabidopsis defective in chloroplast photorelocation movement, we isolated six mutant clones in which chloroplasts gathered at the bottom of the cells and did not distribute throughout cells. These mutants, termed chloroplast unusual positioning (chup), were shown to belong to a single genetic locus by complementation tests. Observation of the positioning of other organelles, such as mitochondria, peroxisomes, and nuclei, revealed that chloroplast positioning and movement are impaired specifically in this mutant, although peroxisomes are distributed along with chloroplasts. The CHUP1 gene encodes a novel protein containing multiple domains, including a coiled-coil domain, an actin binding domain, a Pro-rich region, and two Leu zipper domains. The N-terminal hydrophobic segment of CHUP1 was expressed transiently in leaf cells of Arabidopsis as a fusion protein with the green fluorescent protein. The fusion protein was targeted to envelope membranes of chloroplasts in mesophyll cells, suggesting that CHUP1 may localize in chloroplasts. A glutathione S-transferase fusion protein containing the actin binding domain of CHUP1 was found to bind F-actin in vitro. CHUP1 is a unique gene identified that encodes a protein required for organellar positioning and movement in plant cells.